Sex differences in outcomes of heart failure in an ambulatory, population-based cohort from 2009 to 2013 - Sun, Louise Y.; Tu, Jack V.; Coutinho, Thais; Turek, Michele; Rubens, Fraser D.; McDonnell, Lisa; Tulloch, Heather; Eddeen, Anan Bader; Mielniczuk, Lisa M. (Canadian Medical Association journal (CMAJ), 2018)
Heart failure remains a substantial cause of morbidity and mortality in women. We examined the sex differences in heart failure incidence, mortality and hospital admission in a population-based cohort. All Ontario residents who were diagnosed with heart failure in an ambulatory setting between Apr. 1, 2009, and Mar. 31, 2014, were included in this study. Incident cases of heart failure were captured through physician billing using a validated algorithm. Outcomes were mortality and hospital admission for heart failure within 1 year of the diagnosis. Probability of death and hospital admission were calculated using the Kaplan–Meier method. The hazard of death was assessed using a multivariable Cox proportional hazard model. A total of 90 707 diagnoses of heart failure were made in an ambulatory setting during the study period (47% women). Women were more likely to be older and more frail, and had different comorbidities than men. The incidence of heart failure decreased during the study period in both sexes. The mortality rate decreased in both sexes, but remained higher in women than men. The female age-standardized mortality rate was 89 (95% confidence interval [CI] 80–100) per 1000 in 2009 and 85 (95% CI 75–95) in 2013, versus male age-standardized mortality rates of 88 (95% CI 80–97) in 2009 and 83 (95% CI 75–91) in 2013. Conversely, the rates of incident heart failure hospital admissions after heart failure diagnosis decreased in men and increased in women. Despite decreases in overall heart failure incidence and mortality in ambulatory patients, mortality rates remain higher in women than in men, and rates of hospital admission for heart failure increased in women and declined in men. Further studies should focus on sex differences in health-seeking behaviour, medical therapy and response to therapy to provide guidance for personalized care.